Climate-NDVI interactions in desertification processes in the semi-arid Central High Plateaus of Algeria - Bourecherouche, Meriem; Staihi, Ameur Laouar (Brawijaya University, 2026)
Desertification in semi-arid regions represents a major environmental challenge driven by the combined effects of climate variability and vegetation degradation. This study assessed desertification dynamics in the Central High Plateaus of Algeria through the integration of precipitation, maximum temperature, and vegetation changes derived from the Normalized Difference Vegetation Index (NDVI). Climatic data were obtained from the NASA POWER database, while satellite imagery was processed using geospatial techniques to analyze land cover dynamics over multiple periods. The results showed a significant decline in precipitation and a marked increase in maximum temperatures, particularly in the southern and southeastern parts of the study area. These changes were associated with a progressive reduction in vegetation cover, as indicated by decreasing NDVI values. The integration of these indicators allowed the development of a desertification index, which revealed a clear spatial gradient of environmental degradation. Low and moderate desertification classes dominated the region, covering more than 80% of the study area, while high and very high desertification remained spatially limited but concentrated in southern zones. Overall, the findings demonstrated that desertification processes were intensifying under the combined influence of climatic stress and vegetation degradation. The integration of climatic indicators and NDVI-based vegetation analysis proved effective for monitoring land degradation and identifying priority areas for sustainable land management in semi-arid environments.